Interaction of dietary fatty acids with tumour necrosis factor family cytokines during colon inflammation and cancer - Hofmanová, Jiřina; Straková, Nicol; Vaculová, Alena Hyršlová; Tylichová, Zuzana; Safaříková, Barbora; Skender, Belma; Kozubík, Alois (Mediators of inflammation, 2014)
Intestinal homeostasis is precisely regulated by a number of endogenous regulatory molecules but significantly influenced by dietary compounds. Malfunction of this system may result in chronic inflammation and cancer. Dietary essential n-3 polyunsaturated fatty acids (PUFAs) and short-chain fatty acid butyrate produced from fibre display anti-inflammatory and anticancer activities. Both compounds were shown to modulate the production and activities of TNF family cytokines. Cytokines from the TNF family (TNF- α, TRAIL, and FasL) have potent inflammatory activities and can also regulate apoptosis, which plays an important role in cancer development. The results of our own research showed enhancement of apoptosis in colon cancer cells by a combination of either docosahexaenoic acid (DHA) or butyrate with TNF family cytokines, especially by promotion of the mitochondrial apoptotic pathway and modulation of NF κ B activity. This review is focused mainly on the interaction of dietary PUFAs and butyrate with these cytokines during colon inflammation and cancer development. We summarised recent knowledge about the cellular and molecular mechanisms involved in such effects and outcomes for intestinal cell behaviour and pathologies. Finally, the possible application for the prevention and therapy of colon inflammation and cancer is also outlined.
Keywords: Animals; Intestinal Mucosa; kolon; apoptóza; zánět; Cytokines; butyráty; Mitochondria; Apoptosis; kyseliny dokosahexaenové; tumor nekrotizující faktory; Neoplasms; nádory; cytokiny; Colon; lidé; Butyrates; Mice; Fatty Acids, Unsaturated; myši; Inflammation; mitochondrie; dieta; Tumor Necrosis Factors; Diet; nenasycené mastné kyseliny; NF-kappa B; zvířata; střevní sliznice; Docosahexaenoic Acids; Humans